Identification of OPN1LW Exon 3 Variants Impairing Red-Cone Function in Color Vision Deficiency - Omar, Shaaban Z.; Karim, Karim J. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The most common form of inherited color blindness is red-green color vision deficiency (CVD), which is frequently caused by mutations in the X-linked OPN1LW gene. Red cone malfunction is linked to mutations in exon 3 of this gene. In this study, the Ishihara test was used to evaluate the color vision of 1500 Kurdish students, ages 13–18. Polymerase chain reaction amplification and Sanger sequencing of OPN1LW exon 3 were performed on 50 students who had been diagnosed with protanopia or protanomaly. Variants (nucleotide changes) were analyzed using Geneious Prime® software. Functional impact of variants was predicted using PolyPhen-2 and SIFT. The study found 30 different nucleotide variations, comprising 63.3% missense mutations, 23.3% silent mutations, and 13.3% frameshift mutations. The most common variants were found c.30G>A (p. Arg10Arg), c.106T>C (p. His35Pro), and c.161_162insG (p. Asp54Gly). SIFT found (57.8%) of variations as deleterious (scoring ≤0.05), but PolyPhen-2 assessed (63.1%) as potentially damaging (score >0.9). ABO blood type was unrelated to CVD risk, although consanguinity and family history were strongly linked to CVD risk. Our study revealed that people with red-green CVD have frequent and possibly harmful mutations in exon 3 of OPN1LW. These results may aid in the molecular characterization of CVD in the Kurdish population and could help develop future diagnostic and treatment approaches.